Relationship of Third Trimester Primigravida Mothers’ Anxiety With Psychosocial Preparedness In Facing Delivery At Kombos Public Health Center at Manado City, North Sulawesi Province - Surati, Juolanda Kristin; Ake , Julianus; Tiwatu , Filia Veronica (Journal of Nursing Science Update (JNSU), 2023)
Anxiety is a type of feeling felt by pregnant mothers, especially in the third trimester of primigravida, due to lack of pregnancy and delivery experience. If it was not intervened, that anxiety could affect the psychosocial preparedness of third-trimester primigravida mothers in facing delivery. This research aimed to determine the relationship of third-trimester primigravida mothers' anxiety with psychosocial preparedness in facing delivery at Kombos Public Health Center, Manado City, North Sulawesi Province. This research was quantitative with a correlational descriptive design by cross-sectional approach. This research was conducted at Kombos Public Health Care Center, Manado City, North Sulawesi Province; the sample was collected using a purposive sampling technique with n = 33 samples based on inclusion and exclusion criteria. This research used a non-parametric statistical test, the Spearman correlation test. There was a significant relationship between third-trimester primigravida mothers’ anxiety with psychosocial preparedness in facing delivery with obtained r-coefficient value of 0.493, which showed a reasonably strong relationship correlation with a p-value of 0.004 that was lesser than alpha significant value < 0.05. There was a significant relationship between third-trimester primigravida mothers’ anxiety and psychosocial preparedness in facing delivery at Kombos Public Health Center, Manado City, North Sulawesi Province.